Combinatorics: ancient and modern - Wilson, Robin J.; Watkins, John J. (Oxford University Press, 2013)
Combinatorics is the branch of discreet mathematics that studies (and counts) permutations, combinations, and arrangements of sets of elements. This book presents a survey of the history of combinatorics and uniquely assembles research in the area that would otherwise be inaccessible to the general reader
Hier auch später erschienene, unveränderte Nachdrucke
Literaturangaben
Keywords: Geschichte; Kombinatorik